Dynamic Response of Rub Caused by a Shedding Annular Component Happening in a Steam Turbine. (28th May 2015) - Chen, J. M.; Jiang, D. X.; Wang, N. F.; An, S. P.
Abstract : Rub caused by a shedding annular component is a severe fault happening in a steam turbine, which could result in a long-term wearing effect on the shaft. The shafting abrasion defects shortened the service life and damaged the unit. To identify the fault in time, the dynamic response of rub caused by a shedding annular component was studied as follows: (I) a rotor-bearing model was established based on the structural features of certain steam turbines; node-to-node contact constraint and penalty method were utilized to analyze the impact and friction; (II) dynamic response of the rotor-bearing system and the shedding component was simulated with the development of rub after the component was dropping; (III) fault features were extracted from the vibration near the bearing position by time-domain and frequency-domain analysis. The results indicate that the shedding annular component would not only rotate pivoting its axis but also revolve around the shaft after a period of time. Under the excitation of the contact force, the peak-peak vibration fluctuates greatly. The frequency spectrum contains two main components, that is, the working rotating frequency and revolving frequency. The same phenomenon was observed from the historical data in the field.